2020
DOI: 10.3390/w12102862
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Trends of Water Storage Observed via Gravity Satellite across Distinct Areas in China

Abstract: Knowledge of the spatiotemporal variations of terrestrial water storage (TWS) is critical for the sustainable management of water resources in China. However, this knowledge has not been quantified and compared for the different climate types and underlying surface characteristics. Here, we present observational evidence for the spatiotemporal dynamics of water storage based on the products from the Gravity Recovery and Climate Experiment (GRACE) and the Global Land Data Assimilation System (GLDAS) in China ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It is well known that snow‐ice fixed in high mountains is the most important source of water storage in the isolated, arid inland regions (Deng et al, 2019; He, Sun, et al, 2020). The melting snow‐ice of the Tianshan Mountains, a huge mountain system stretching across central Asia, is the main source of water to nourish the downstream oases and grasslands (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that snow‐ice fixed in high mountains is the most important source of water storage in the isolated, arid inland regions (Deng et al, 2019; He, Sun, et al, 2020). The melting snow‐ice of the Tianshan Mountains, a huge mountain system stretching across central Asia, is the main source of water to nourish the downstream oases and grasslands (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(2021) adopt a new metric to rationalize the meanings of the trend term in TWS globally. Many studies have also been conducted to investigate the water storage changes in China and their causes (He et al., 2020; Lv et al., 2021; X. Wang et al., 2020; Xu et al., 2019). These studies showed consistent findings on the spatial heterogeneity of regional water storage in China but presented different interpretations on the attribution of water storage change.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in evapotranspiration, atmospheric water vapor, and precipitation cause changes in the global hydrological cycle (IPCC, 2013), which in turn affect subsurface hydrologic dynamics and lead to changes in the recharge and discharge of aquifers (Smerdon, 2017). In addition, the loss of groundwater storage causes problems such as land subsidence, reductions in spring water, and reductions in domestic and agricultural water supply (Konikow and Kendy, 2005;Feng et al, 2013;Gong et al, 2018;Deng et al, 2019;He et al, 2020). At present, there are few studies on the impact of climate change on groundwater storage, especially in areas that are heavily influenced by human activities and sensitive to climate change.…”
Section: Introductionmentioning
confidence: 99%